(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
In this paper I have shared some of my experiences on how to handle case studies in teaching with the intent to facilitate more discussions during our meeting over the two day conference on research informed teaching at Samtse College of Education organized by the Royal University of Bhutan in October 2014. We know that case studies are stories used as knowledge and skill transfer vehicles by which a lot of real life scenario is brought into the classroom to be discussed by the students and instructors. How we use case studies dependsuponthe objectives and the format of the course. My experience suggest that if it is a regular university dictated course with astrict timetable (one hour period everyday per subject) with pre-identified contents and has a large class size,it is not normally possible or at least not meaningfully efficient to go beyond the use ofsimple cases that will only help to illustrate the subject concepts and demonstrate afew practical aspects. However, if the class is smaller and the course is more discussion based with properly designed sessions, we choose to use cases through complex analysis thereby guiding the students in a step-wise fashionin the analysis of relevant information, problem identification and option evaluation. Whatever may be the format of the course or the class in which we use case studies, it is important that we, as case teachers, prepare ourselves well and know all the issues involved in the case, prepare questions in advance and prompt discussions and debate in the class, and anticipate where students might run into problems. Needless to mention that we encounter within the class, few or even all students findingthemselves out of place when case studies are used; it particularly true in the Bhutanese situation as our teaching and learning system is historically predominant with the traditional lecture method. To overcome such problems, it is essential to prepare students for case based learning methods. We must know about our students backgrounds in advance so that wecan productively draw on their areas of expertise, experiences and personalities to enhance the discussionandenrich learning across the board as facilitators rather than acting as a traditional teacher[1].